ANALISIS MANAJEMEN KRISIS DI KAWASAN WISATA ALAM TELAGA NGEBEL PONOROGO - Deviona Ayu Larasati; Joko Mijiarto (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2026)
Indonesia faces the potential risk of natural disasters such as landslides and extreme weather. Lake Ngebel is one of the attractions with this level of vulnerability. This study aims to analyze the preparedness of natural disaster crisis management in the Lake Ngebel tourist area. This study used a descriptive qualitative approach, with the research location at Lake Ngebel, Ponorogo. The research subjects included the Regional Disaster Management Agency as key informants, tourism managers as primary informants, and tourists as supporting informants. Data collection techniques were carried out through in-depth interviews, observation, and documentation, with data analysis carried out through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of crisis management is not optimal. In the pre-crisis phase, the unavailability of disaster hazard maps and ineffective risk communication indicate low preparedness, even though evacuation routes are available. In the crisis phase, coordination and emergency response were quite effective according to standard operating procedures and supported by simulation training. In the post-crisis phase, an evaluation has been conducted, but its implementation requires strengthening. Overall, crisis management still tends to be reactive.